PENERAPAN SISTEM PERADILAN PIDANA ANAK DALAM KAITAN DENGAN HAK-HAK ASASI ANAK ( STUDI DI PENGADILAN NEGERI KISARAN) - Fahrul Rizal (Smart Education, 2022)
The Juvenile Criminal Justice System is the entire process of Settlement of Child Cases in conflict with the law, starting from the investigation stage to the mentoring stage after the child undergoes the criminal law process. Implementation of Criminal Sanctions for Actions Against Children According to Law No. 11 of 2012 concerning the Juvenile Criminal Justice System, is an